2017
DOI: 10.1212/wnl.0000000000004105
|View full text |Cite
|
Sign up to set email alerts
|

Patients with ALS show highly correlated progression rates in left and right limb muscles

Abstract: Objective:Amyotrophic lateral sclerosis (ALS) progresses at different rates between patients, making clinical trial design difficult and dependent on large cohorts of patients. Currently, there are few data showing whether the left and right limbs progress at the same or different rates. This study addresses rates of decline in specific muscle groups of patients with ALS and assesses whether there is a relationship between left and right muscles in the same patient, regardless of overall progression.Methods:A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…The unilateral trial design allowed direct comparison of treated and untreated leg muscle strength, removing the variability in bilateral studies due to patient variability in strength decline. We have shown that muscle groups on each side of the body have remarkably similar progression rates in individual patients with ALS 39 . Therefore, we predicted that identical progression rates would indicate no treatment effect, whereas a slower decline in the treated leg compared with the untreated leg would suggest a positive graft effect.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The unilateral trial design allowed direct comparison of treated and untreated leg muscle strength, removing the variability in bilateral studies due to patient variability in strength decline. We have shown that muscle groups on each side of the body have remarkably similar progression rates in individual patients with ALS 39 . Therefore, we predicted that identical progression rates would indicate no treatment effect, whereas a slower decline in the treated leg compared with the untreated leg would suggest a positive graft effect.…”
Section: Resultsmentioning
confidence: 80%
“…ALS is a heterogeneous disease in which progression rates in individual patients can vary extensively 40 . However, we have shown in a large patient cohort that the progression rate in individual patients with ALS is remarkably similar for functional muscle groups on each side of the body 39 . Directly comparing treated and untreated legs for individual patients removes the variability seen in bilateral studies due to different progression rates.…”
Section: Discussionmentioning
confidence: 83%
“…This apparent discrepancy may be related to the sample's relatively long disease duration (mean 3 years) as there is a high degree of left and right clinical muscle decline over the course of time (Rushton et al, 2017). In this instance, we refrained from the calculation of MRC scale inter-side differences, which seems to be not promising in long-standing disease (Rushton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This ALS clinical trial design approach, based on comparing sides in the same patient, has recently been proposed by Rushton et al (2017) after demonstrating that progression rate in the left and right limb muscles of ALS sufferers shows a high degree of correlation; this progression is not related to the first muscle to begin declining and, on average, the right and left sides decline at the same rate following onset. For these reasons, an approach using one side for treatment and the other as a simultaneous internal control is perfectly feasible for stem cell transplant trials.…”
Section: Discussionmentioning
confidence: 99%